Seva, saviour and state :caste politics, tribal welfare and capitalist development - Srivatsan, R. (Routledge, 2019)
This book provides a unique understanding of the concept and practice of seva (service) in modern India. It examines social reform, key ameliorative programmes, seva organisations, nationalist politics and colonial anthropology to show the critical linkages between caste politics, tribal welfare and capitalist development. Drawing upon archival research and field interviews, the author establishes a critical dialogue with both historiography and ethnography. Further, he explores how the works of Gandhi, Nehru, Ambedkar, Gokhale, and others functioned in the political discourses and practices of their time. This lucid and comprehensive study will interest scholars and researchers in political theory, modern Indian history, sociology and social anthropology, Dalit and tribal studies, and cultural studies.